2018
DOI: 10.5539/ijel.v8n4p232
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Vygotsky’s Socio-Cultural Theory in Second Language Acquisition

Abstract: The purpose of this study is to explore Vygotsky's contribution to the socio-cultural theory in the field of education in general, and applied linguistics in particular. The study aims to elaborate the impact of social-cultural theory in the existing body of literature. The study also reviews implications and applications of socio-cultural theory in second language acquisition (SLA). Moreover, this study also critiques the basic concepts of the theory and how far these concepts have been implicated in the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…These learning activities provide an opportunity for students to communicate with peers, simulated and real patients. Vygotsky puts forward the concept of Zone Proximal Development (ZPD) in which a learner's level of potential development is determined through adult guidance or collaborative work with more capable peers [17]. Through guided participation, learning and development takes place in a social context between learner and teacher [12] allowing medical students to enhance their English language skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These learning activities provide an opportunity for students to communicate with peers, simulated and real patients. Vygotsky puts forward the concept of Zone Proximal Development (ZPD) in which a learner's level of potential development is determined through adult guidance or collaborative work with more capable peers [17]. Through guided participation, learning and development takes place in a social context between learner and teacher [12] allowing medical students to enhance their English language skills.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, students observed that in both the learning and healthcare environment, English language is used in a professional setting among other healthcare professionals and for patient care. Vygotsky proposed that mediation (a tool) is often used by learners to resolve a problem or achieve a target, and hence language is considered a signi cant tool for learners to develop the knowledge that they require [17]. In this context, medical students reminded educators that the English language, as a communication tool, was crucial for person-centred care whereby communication skills is crucial for patient engagement and safety of care.…”
Section: Discussionmentioning
confidence: 99%
“…The learner learns promptly and actively with the presence of MKO compared to when the learner learns independently. Thus, it shows that there is a big difference in the learners' development 35 .…”
Section: Social Development Theorymentioning
confidence: 95%
“…Vygotsky's Social Development Theory is adapted into the proposed model. Despite the interest in Vygotsky's theory 29,34,35,44 , most research generally focuses on the other component, ZPD. Therefore, there is still a lack of explanation on the concept of MKO.…”
Section: Mko Component Frommentioning
confidence: 99%
“…However, learning cannot take place in isolation and hence adult mediation occupies a central position in the process. To articulate the space in which learning occurs, Vygotsky introduced the Zone of Proximal Development (ZPD) -"a construct that outlines the distance between the level of actual development as an independent learner and the level of the potential development achieved using solving problems with the support of an adult guide and facilitator or in collaboration with peers who are comparatively more capable", (Vygotsky, 1978: 86) (for an intensive critical review of the influence of Vygostky on SLA modern research see Pathan, et al 2018). Later, Bakhtin's (1981) (who was also a contemporary of Vygotsky's but outlived him) inspired by Vygotsky's Sociocultural Theory of learning, propounded the philosophy of dialogism arguing it is ingrained in human consciousness, and the internalization of the same occurs utilizing interactive activities involving thoughts and languages (Teo, 2019).…”
Section: Introductionmentioning
confidence: 99%